Dietary Regulation of the Crosstalk between Gut Microbiome and Immune Response in Inflammatory Bowel Disease - Yao, Qianqian (Foods, 2021)
Inflammatory bowel disease (IBD), a chronic, recurring inflammatory response, is a growing global public health issue. It results from the aberrant crosstalk among environmental factors, gut microbiota, the immune system, and host genetics, with microbiota serving as the core of communication for differently-sourced signals. In the susceptible host, dysbiosis, characterized by the bloom of facultative anaerobic bacteria and the decline of community diversity and balance, can trigger an aberrant immune response that leads to reduced tolerance against commensal microbiota. In IBD, such dysbiosis has been profoundly proven in animal models, as well as clinic data analysis; however, it has not yet been conclusively ascertained whether dysbiosis actually promotes the disease or is simply a consequence of the inflammatory disorder. Better insight into the complex network of interactions between food, the intestinal microbiome, and host immune response will, therefore, contribute significantly to the diagnosis, treatment, and management of IBD. In this article, we review the ways in which the mutualistic circle of dietary nutrients, gut microbiota, and the immune system becomes anomalous during the IBD process, and discuss the roles of bacterial factors in shaping the intestinal inflammatory barrier and adjusting immune capacity.